Improved Wait Times from Abnormal Diagnostic Imaging to Biopsy of Suspicious Breast Lesions at King Abdulaziz University Hospital - Laila K. Ashkar, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Timely coordinated breast biopsies following abnormal diagnostic breast imaging reduces patient anxiety and may optimize breast cancer prognosis. Two different pathways have been used in the breast unit at the Radiology Department of King Abdulaziz University Hospital. Before September 2009, all patients who had abnormal breast imaging were sent back to their referring physician, who would then request the necessary biopsy. In September 2009, we proposed the shortened pathway; and coordinated the necessary biopsy directly at our unit, instead of sending the patients back to their physician. This has saved them many weeks of agony and confusion navigating through the medical system to arrange appointments for surgical consultation and radiological biopsy. This study aimed to assess the wait time from abnormal breast imaging to the time of the biopsy. A retrospective study included an analysis of 51 consecutive breast biopsies performed before 2009, compared to 51 biopsy patients after implementing the improved pathway in 2009. It concluded that the expedited pathway reduced the wait time from 42 to 14 days until final diagnosis. To ensure that targets for timeliness are realized, this improved and efficient pathway of care was adapted permanently and has been ongoing since then.